Targeting the undruggable: an interview with Leila Akkari on fighting cancer by rewiring cells (Nature Portfolio, 2021)
Leila Akkari began her independent career in 2017 as an Assistant Professor at the Netherlands Cancer Institute in Amsterdam after working at Memorial Sloan Kettering Cancer Center in NYC. Two years ago, she was selected as one of the junior members of the Oncode Institute, a virtual group of cancer research labs based on the Netherlands. In this short Q&A, she tells us about her research and how her diverse background has helped her as a scientist. Dr. Akkari also shares some great pointers on the biggest hurdles women in STEM face and tips to overcome them.